Gender Aesthetics and Symbolic Tension in Syofyani’s Pasambahan Dance: Negotiating Honor, Hospitality, and Cultural Identity - Virginia Aulia, Tiara; Indrayuda, Indrayuda (Universitas Negeri Medan, 2025)
This study critically examines the movement techniques and body postures in Syofyani’s Pasambahan Dance by exploring how the values of honor and hospitality are constructed, performed, and negotiated within the Minangkabau cultural context. Rather than assuming harmony between movement and cultural values as fixed, this study questions how gender construction and bodily symbolism in dance operate within a matrilineal society that paradoxically privileges masculine roles in public performance spaces. This research employs a descriptive qualitative approach with data collected through participant observation, in-depth interviews, and visual documentation at the Syofyani Dance Studio in Padang, West Sumatra. The researcher was present not only as an external observer but also as a limited participant in rehearsals and artistic discussions, in order to understand the meaning-making process through the body and movement.Findings show that male dancers' movement techniques, derived from pencak silat, exhibit protective, dominant, and assertive traits, while female dancers express gentleness and deference through movements inspired by silat bunga. However, a critical reading reveals that this gender division does not necessarily reflect Minangkabau gender reality but rather represents a symbolic negotiation that evolves with changing social dynamics and modern aesthetic expectations. Furthermore, symbols such as the carano and betel leaves are not always received with a singular meaning. Younger dancers, especially those living in urban areas, interpret these symbols as formalities or even folklorization, rather than as expressions of spirituality. When the dance is performed at tourism events or modern receptions, its meaning shifts from a ritual of respect to a visual attraction. This study affirms that Pasambahan Dance is not merely an aesthetic medium but also a discursive arena where values, identities, and ideologies are negotiated. By combining dance analysis and performance ethnography, this research contributes to the discourse on cultural preservation, performative critique, and arts education that is both contextual and reflective.